In-vitro sperm immobilization activity and biocompatibility study of NVD terpolymer - Gupta, Sachin; Yadav, Ruchi; Thakur, Mayank (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Boronate derivatives have been used in affinity chromatography for separation of cells based on their glycoprotein content. Boronate containing polymers when used intravaginally before sexual intercourse could bind to the glycoproteins present on sperm cell surface and render them immobile, which potentially may work as female-controlled contraceptive. To study this hypothesis NVD terpolymer which contains boronic acid was studied on goat sperm and its biocompatibility was accessed on NIH3T3 fibroblast. Methods: Sperm motility study was carried out on goat sperm cells. The study was divided into two groups, test group (NVD terpolymer in simulated vaginal fluid) and negative control (simulated vaginal fluid only) performed using Sander-crammer assay. In the test group, the study was started from 0.1 % of the polymer solution, until the half of the sperms became non-motile as compared to normal control. The biocompatibility study was performed by culturing the NIH3T3 fibroblast with different concentrations of NVD polymer, followed by cell viability assay by performing 3-(4, 5-dimethylthiazol-2-Yl)-2, 5-diphenyltetrazolium bromide (MTT) assay at 6, 12 and 24 hour spectrophotometrically. Results: Sander-crammer assay resulted in significant (P-value < 0.05) decrease in motile sperm count in test group when compared to control. At 7.5 % concentration, the half of the sperms rendered immobile, and this was termed as effective concentration 50 (EC50). In-vitro biocompatibility study using NIH3T3 fibroblasts culture and MTT assay with cultured cells at 6, 12 and 24 hour, revealed that the polymer is biologically compatible as there were no significant change (P-value < 0.05) in the absorbance. Conclusions: Boronate containing polymer, such as NVD terpolymer has in-vitro sperm immobilizing activity in goat sperm model, with further research in this area could yield a potential female control contraceptive agent.